Pengembangan Bahan Ajar Menulis Teks Biografi Berpendekatan Life Base Learning untuk Siswa Kelas X Sekolah Menengah Kejuruan (SMK) - Nuri Riskian; Taufik Dermawan (JoLLA: Journal of Language, Literature, and Arts, 2021)
Abstract: Development of teaching materials to write biographical text choosing a life-based learning approach is intended for students of grade X Vocational High School (SMK). This development is considered capable of being a solution to the lack of teaching materials to write biographical text for vocational schools. The selection of life-based learning approaches is considered by researchers to be able to bring learning closer to life. An approach that is in accordance with the characteristics of The Indonesian Language that becomes a science expert. Qr-code presented in the development of this book helps students understand the concepts, materials of teaching materials, articles, concepts of life-based learning, and activities presented. This study uses the ADDIE model (analysis, design, develop, implement, and evaluate). Needs analysis and curriculum become the beginning of knowing the urgency of need analysis. Analysis of student needs at SMKN Darul Ulum shows the need in the development of teaching materials with a percentage of 80%. Product development by arranging teaching material development instruments according to previous needs analysis. Validity test is conducted to know that the teaching materials developed in accordance with the material expert validation test instrument, the validity of learning media, and the validity of field learners. Based on the results of the validity test, the following percentages were obtained: material validity 99.01%, media validity 91.04%, and lastly the validity of field learners 95.52%. Seeing the results, the teaching materials developed by the researchers get very valid results and can be implemented. Keywords: teaching materials, biographical text, Life Based Learning, vocational high school Abstrak: Pengembangan bahan ajar menulis teks biografi memilih pendekatan life-based learning ini ditujukan untuk siswa kelas X Sekolah Menengah Kejuruan (SMK). Pengembangan ini dinilai mampu menjadi solusi minimnya bahan ajar menulis teks biografi untuk SMK. Pemilihan pendekatan life-based learning dinilai peneliti mampu mendekatkan pembelajaran pada kehidupan. Pendekatan yang sesuai dengan ciri khas Bahasa Indonesia yang menjadi penghela ilmu pengetahuan. QR-code yang dihadirkan dalam pengembangan buku ini membantu siswa memahami konsep, materi bahan ajar, artikel, konsep life-based learning, dan aktivitas yang dihadirkan. Penelitian ini menggunakan model ADDIE (analysis, design, develop, implement, and evaluate). Analisis kebutuhan dan kurikulum menjadi awal mengetahui urgensi analisis kebutuhan (need analysis). Analisis kebutuhan siswa di SMKN Darul Ulum menunjukan kebutuhan dalam pengembangan bahan ajar dengan persentase 80%. Pengembangan produk dengan menyusun instrumen pengembangan bahan ajar sesuai analisis kebutuhan sebelumnya. Uji Validitas dilakukan untuk mengetahui bahwa bahan ajar yang dikembangkan sesuai dengan instrumen uji validasi ahli materi, validitas media pembelajaran, dan validitas pembelajar lapangan. Berdasarkan hasil uji validitas maka diperoleh persentase sebagai berikut yakni: validitas materi 99,01%, validitas media 91,04%, dan terakhir validitas pembelajar lapangan 95,52%. Melihat hasil yang ada maka bahan ajar yang dikembangkan oleh peneliti mendapatkan hasil sangat valid dan dapat diimplementasikan. Kata kunci: bahan ajar, teks biografi, Life Based Learning, sekolah menengah kejuruan